2008
DOI: 10.1007/s11440-008-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

A thermomicromechanical approach to multiscale continuum modeling of dense granular materials

Abstract: A new method is proposed for the development of a class of elastoplastic thermomicromechanical constitutive laws for granular materials. The method engenders physical transparency in the constitutive formulation of multiscale phenomena from the particle to bulk. We demonstrate this approach for dense, cohesionless granular media under quasi-static loading conditions. The resulting constitutive law-expressed solely in terms of particle scale properties-is the first of its kind. Micromechanical relations for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 37 publications
4
62
0
Order By: Relevance
“…Prior to collapse force chains accumulate stored potential energy and this process continues until the force chains reach their peak load, after which buckling occurs and the force chains experience a loss in load-carrying capacity [14]. Furthermore, Tordesillas & Muthuswamy [15] showed that force chain buckling can be elastic or plastic depending on the state of the contact points. Hence, failure is associated with buckling of the strong force chains and  provides a resistance to buckling.…”
Section: Simulation Parameters and Specimen Generationmentioning
confidence: 99%
“…Prior to collapse force chains accumulate stored potential energy and this process continues until the force chains reach their peak load, after which buckling occurs and the force chains experience a loss in load-carrying capacity [14]. Furthermore, Tordesillas & Muthuswamy [15] showed that force chain buckling can be elastic or plastic depending on the state of the contact points. Hence, failure is associated with buckling of the strong force chains and  provides a resistance to buckling.…”
Section: Simulation Parameters and Specimen Generationmentioning
confidence: 99%
“…Load-carrying capacity and energy dissipation form the two halves of mathematical formulations that relate the deformation to the stress in a dissipative material (i.e., continuum models). To achieve reliable and robust predictions, such models must incorporate the kinematics of those rearrangement events which are chiefly responsible for energy dissipation (i.e., internal variables or plastic strains [20,23,26,36]). Knowledge of which conformational transitions are likely to occur when a force chain buckles and their associated probabilities is an essential and heretofore missing element in continuum models [26,30].…”
Section: Fig 3 (Color Online)mentioning
confidence: 99%
“…Unravelling the details of these mesoscopic structures and associated frictional rearrangements, and their impact on bulk mechanical response-particularly on the development of failure-presents a great scientific challenge [7,18,20,21]. Indeed, although granular materials have stimulated intense research activity for decades [5][6][7][8], robust predictions of their mechanical behavior under load remain elusive [12,[22][23][24][25][26]. To date, a crucial missing element that limits prediction and control of dense granular behavior, particularly that of inelastic deformation and failure, is a precise understanding of the interplay between the dynamics of prevalent and * Corresponding author: atordesi@ms.unimelb.edu.au persistent particle rearrangements and the evolution to failure of key functional mesoscopic structures, epitomized by major load-bearing force chains [10,14,18,[26][27][28][29][30][31][32]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the above studies focused on characterizing the fabric tensor in assemblies of particles. In addition, Tordesillas and Muthuswamy [23] investigated the evolution of both the fabric and contact force in dense granular materials from the perspective of complex networks.…”
Section: Introductionmentioning
confidence: 99%